Interview with Oleg Chaban about medical psychology - Chaban, Oleg (Psychosomatic Medicine and General Practice, 2017)
Interview with Head of the Department of Psychosomatic Medicine and Psychotherapy in Bogomolets National Medical University and editor-in-chief of the journal devoted to medical psychology, medical psychologists and psychotherapy.